Characterizing Genetic Regulatory Elements in Ovine Tissues - Davenport, Kimberly M.; Massa, Alisha T.; Bhattarai, Suraj; McKay, Stephanie D.; Mousel, Michelle R.; Herndon, Maria K.; White, Stephen N.; Cockett, Noelle E.; Smith, Timothy P. L.; Murdoch, Brenda M.; , on behalf of The Ovine FAANG Project Consortium (Frontiers in Genetics, 2021)
The Ovine Functional Annotation of Animal Genomes (FAANG) project, part of the broader livestock species FAANG initiative, aims to identify and characterize gene regulatory elements in domestic sheep. Regulatory element annotation is essential for identifying genetic variants that affect health and production traits in this important agricultural species, as greater than 90% of variants underlying genetic effects are estimated to lie outside of transcribed regions. Histone modifications that distinguish active or repressed chromatin states, CTCF binding, and DNA methylation were used to characterize regulatory elements in liver, spleen, and cerebellum tissues from four yearling sheep. Chromatin immunoprecipitation with sequencing (ChIP-seq) was performed for H3K4me3, H3K27ac, H3K4me1, H3K27me3, and CTCF. Nine chromatin states including active promoters, active enhancers, poised enhancers, repressed enhancers, and insulators were characterized in each tissue using ChromHMM. Whole genome bisulfite sequencing (WGBS) was performed, to determine the complement of whole genome DNA methylation with the ChIP-seq data. Hypermethylated and hypomethylated regions were identified across tissues and these locations were compared with chromatin states to better distinguish and validate regulatory elements in these tissues. Interestingly, chromatin states with the poised enhancer mark H3K4me1 in spleen and cerebellum, and CTCF in liver displayed the greatest number of hypermethylated sites. Not surprisingly, active enhancers in liver and spleen, and promoters in cerebellum, displayed the greatest number of hypomethylated sites. Overall, chromatin states defined by histone marks and CTCF occupied approximately 22% of the genome in all three tissues. Further, liver and spleen displayed the greatest percent of active promoter (65%) active enhancer (81%) states in common, and liver and cerebellum displayed the greatest percent of poised enhancer (53%), repressed enhancer (68%), hypermethylated sites (75%), and hypomethylated sites (73%) in common. In addition, both known and de novo CTCF binding motifs were identified in all three tissues, with the highest number of unique motifs identified in cerebellum. In summary, this study has identified the regulatory regions of genes in three tissues that play key roles in defining health and economically important traits and has set the precedent for the characterization of regulatory elements in ovine tissues using the Rambouillet reference genome.